Comparison of Transmission Loss Allocation Methods and Prediction of Losses in Deregulated Power Systems - Matemeke Edwinah Maredi, Matemeke Edwinah Maredi (2010)
Transmission losses are a significant component of the amount of power to be generated in order to meet the power demand. Today, in competitive electric energy markets operating under pool-based, bilateral contracts or hybrid model, transmission losses must be allocated among the market participants.